+0  
 
0
238
2
avatar

Differentiate with respect to x: y=4x-5ax^(-5)

Guest Oct 1, 2017
 #1
avatar
+1

Possible derivation:
d/dx(-(5 a)/x^5 + 4 x)

Differentiate the sum term by term and factor out constants:
 = -5 a (d/dx(1/x^5)) + 4 (d/dx(x))

Use the power rule, d/dx(x^n) = n x^(n - 1), where n = -5: d/dx(1/x^5) = d/dx(x^(-5)) = -5 x^(-6):
 = 4 (d/dx(x)) - (-5)/x^6 5 a

Simplify the expression:
 = (25 a)/x^6 + 4 (d/dx(x))

The derivative of x is 1:
 = (25 a)/x^6 + 1 4

Simplify the expression:
= 4 + (25 a)/x^6

Guest Oct 1, 2017
 #2
avatar+87301 
+1

 y = 4x - (5a)x^(-5)  

 

dy / dx  =  4 + (25a)x^(-6)

 

 

cool cool cool

CPhill  Oct 1, 2017

14 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.